Identification and Characterization of Begomoviruses-Whitefly Complex Infecting Soybean in Pakistan - Kanwal, Seema; Riaz, Hasan; Ashfaq, Muhammad; Saeed, Shafqat; Zia, Faheem; Khan, Sabeeh; Raza, Sufyan; Imran, Muhammad; Afzal, Muhammad; Deeba, Farah; Yasin, Mudassar; Rafeeq, Farzana; et al. (Journal of Agriculture and Biology, 2024)
Begomoviruses are ssDNA viruses exclusively transmitted by whitefly Bemisia tabaci. The begomoviruses-whitefly complex is responsible for inflicting severe damage to the crops. Soybean crop, new to Pakistan, remains unexplored regarding the virus-vector complex therefore present study was aimed to identify and determine the genetic variability of begomoviruses infecting soybean crop along with the whitefly mitotype(s) involved in their transmission. Soybean plants displaying symptoms of begomoviruses infection were collected and total genomic DNA was extracted from both symptomatic leaves and viruliferous whiteflies. Diagnostic PCR was employed to detect begomoviruses followed by whole genome amplification of begomoviruses by rolling circle amplification technique. The RCA products were subsequently cloned and sequenced. The partial cytochrome oxidase subunit I (COI) gene of the whiteflies was amplified and directly sequenced in both orientations. The sequences were assembled using Geneious R10 software and BLAST analysis was conducted through online NCBI web portal. Similarity index matrix and phylogenetic trees were constructed using sequence demarcation tool (SDT), MEGA11 and MrBayes software packages. The results proved 98% similarity of begomovirus Multan isolate with Tomato Leaf Curl New Delhi virus (ToLCNDV). The COI gene sequence of Bemisia tabaci showed 99.9% similarity with mitotype Asia II-I found in Pakistan. The study confirmed the infection of ToLCNDV and Asia-II-I presence on soybean in Multan, Pakistan and would be useful in understanding begomoviruses-whitefly complexes in Soybean crop and Southern Punjab.
Keywords: Identification; Begomoviruses; Bemisia tabaci; Phylogenetic analysis; Genetic variability; Soybean